A new species of the genus Watsonidia Toulgoët, 1981 (Lepidoptera, Erebidae, Arctiini): example of polymorphism in the Amazon of Peru - Grados, Juan (Zootaxa, 2019)
A new species of the genus Watsonidia Toulgoët, from the Amazon region of Peru, is described, with two morphotypes. Characters of males and female genitalia of both morphotypes and the genetic analyses (COI) that support the polymorphism of the species are provided. The habitus of males and females is also illustrated.